PENERAPAN METODE TARGET COSTING DALAM PERENCANAAN BIAYA PRODUKSI UNTUK OPTIMALISASI LABA PADA UMKM DENDENG SAPI ACEH DI BANDA ACEH - Affiqah, Cut; Fuadi, Raida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this research was to apply the target costing to the Aceh Cow Beef Jerky Community so that it addressed the difficulties of Aceh cow beef jerky producers in managing production costs and also helped increase the profits that the company could obtain. The type of research used is descriptive comparative research in the form of empirical studies with quantitative approaches. The population in this research were all the Aceh Cow Beef Jerky Community in Banda Aceh with research samples namely Rencong Aceh, Bungong Jaroe, and Gunung Seulawah. The sampling method used is non-probability sampling with a purposive sampling technique. The data sources used are primary data and secondary data. Data collection techniques used were interviews, observation, and documentation. In analyzing the data used target costing and value engineering calculations. Then compare the results of the profit target before and after the use of the target costing method. The results of this study indicate that after applying the target costing method, an increase in profit from the specified profit target is Bungong Jaroe of 2.44% and Rencong Aceh of 0.57%.